The influence of absorptive capacity and technology park services on the relationship between social capital and technology transfer performance - Rahimi, Abidin (2014)
The establishment of technology parks serves as a medium to promote the technology transfer processes in the high technology sector that plays a role to catalyze the productivity and growth of the national economy. Previous studies revealed that although there is anticipation of technology transfer activities among the companies within the technology parks, there is a limitation in the ability of local knowledge workers to produce new technology. Social capital and absorptive capacity were highlighted as essential in ensuring the success of technology transfer. This study examined the impact of technology park services on the relationships among social capital, absorptive capacity and technology transfer performance. It also focused on the influence of absorptive capacity on the association between social capital and technology transfer performance. A theoretical framework was constructed based on the perspective of the knowledge-based view theory to describe the relationships among these variables. Data was collected through a survey of 358 high technology companies operating in four selected technology parks in Malaysia. Out of the 97 questionnaires returned only 90 were usable bringing the response rate to about 25%. Using descriptive and inferential statistics, the data was tested and proven to support the research framework. Pearson correlation and regression analyses established that both social capital and absorptive capacity are essential to ensure high performance of technology transfer. There are mediating effects of absorptive capacity on the relationships between the dimensions of social capital and technology transfer performance. The results also demonstrated that technology park services have moderating effects on the strength of the relationships between the dimensions of social capital and technology transfer performance; as well as between absorptive capacity and technology transfer performance